STRENGTHENING DIGITAL LEARNING IN INDONESIAN PRIMARY SCHOOLS: A QUALITATIVE STUDY OF PPG GRADUATES - Linda Astriani; Dewi Setiyaningsih; Ahmad Susanto; Sri Immawati; Sodikin Sodikin; Rikaro Ramadi; Ratna Nur Krismawati (Universitas Majalengka, 2026)
Digital transformation in primary education requires teachers to possess integrated technological and pedagogical competencies in order to design effective learning environments. However, disparities in digital readiness remain a significant challenge in many primary schools. This study aims to describe the role of graduates of the Teacher Professional Education Program (PPG) in strengthening digital learning practices in primary schools, to identify the challenges they encounter, and to examine the strategies employed to optimize the use of instructional technology. This research adopted a descriptive qualitative approach, with data collected through classroom observations, in-depth interviews, and documentation. Data were analyzed using an interactive analysis process consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that PPG graduates contribute to improving the quality of digital lesson planning, the use of interactive learning media, and the implementation of technology-based assessment that supports students’ conceptual understanding and engagement. Digital learning practices also enhance instructional clarity and enrich students’ learning experiences through the use of diverse digital learning resources. Nevertheless, limited access to digital devices, unstable internet connectivity, and insufficient continuous professional development remain major barriers to effective digital learning implementation. This study concludes that PPG graduates play an important role as agents of digital transformation in primary education; however, the effectiveness of this role is highly dependent on systemic school support, infrastructure readiness, and the sustainability of teachers’ professional development.